Trends in malignant melanoma mortality in 31 countries from 1985 to 2015. (1st December 2020) - Yang, D.D.; Salciccioli, J.D.; Marshall, D.C.; Sheri, A.; Shalhoub, J.
Summary: Background: Malignant melanoma (MM) causes the highest absolute number of deaths among skin cancers. An up‐to‐date analysis of international MM mortality trends is required for assessing the burden of disease, and may support the assessment of the effectiveness of new diagnostic, therapeutic and preventative strategies. Objectives: To report MM mortality trends between 1985 and 2015 using the World Health Organization (WHO) Mortality Database. Materials and methods: We used country‐level MM mortality data from the WHO Mortality Database for all countries with high usability death registration data. Mortality trends were described using Joinpoint regression modelling. Results: Thirty‐one countries met the inclusion criteria. All countries, except the Czech Republic, demonstrated increased age‐standardized death rates (ASDRs) in males over the observation period. More countries exhibited decreased or stable MM mortality in females. The median mortality rate for 2013–2015 was 2·57 deaths per 100 000 for males and 1·55 per 100 000 for females. Australia and Norway had the highest ASDRs for males (5·72 per 100 000 and 4·55 per 100 000, respectively). Norway and Slovenia had the highest ASDRs for females (3·02 per 100 000 and 2·58 per 100 000, respectively). MM mortality was greater for males than females in all countries, with sex disparity increasing across the period. Disparity in mortality between older and younger cohorts in several countries was also found. Conclusions: An overall increase in MM mortality over the past 30 years was observed. However, there was notable variation in mortality trends between countries, as well as between males and females, and between different age groups.